2019
DOI: 10.1016/j.mambio.2019.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Density and spatio-temporal behaviour of Geoffroy's cats in a human-dominated landscape of southern Brazil

Abstract: Geoffroy"s cat is a small Neotropical felid, seemingly abundant throughout most of its range and exhibiting considerable ecological plasticity. In Brazil, the species is restricted to the Pampas, one of the most threatened biomes in the country, where information on its ecology is scarce. Here we report the first assessments of its density, habitat selection, and activity patterns in Brazil. The study was conducted in humandominated landscape at the extreme south of the country. Using Spatially Explicit Captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…org/10.22201/ib.20078706e.2023.94.5243 These above-mentioned authors reported values of capture rate 10 times lower than our study. In the case of Geoffroy's cat, the capture rate was similar to that reported by Tirelli et al (2019) for grasslands in southern Brazil, but 2 to 4 times higher compared to other sites (Caruso et al, 2017(Caruso et al, , 2020Cravino & Brazeiro, 2021). These differences may relate to good habitat conditions in highland grassland, providing shelter for these species and resulting in higher densities in this habitat (Cravino & Brazeiro, 2021).…”
Section: Discussionsupporting
confidence: 72%
“…org/10.22201/ib.20078706e.2023.94.5243 These above-mentioned authors reported values of capture rate 10 times lower than our study. In the case of Geoffroy's cat, the capture rate was similar to that reported by Tirelli et al (2019) for grasslands in southern Brazil, but 2 to 4 times higher compared to other sites (Caruso et al, 2017(Caruso et al, , 2020Cravino & Brazeiro, 2021). These differences may relate to good habitat conditions in highland grassland, providing shelter for these species and resulting in higher densities in this habitat (Cravino & Brazeiro, 2021).…”
Section: Discussionsupporting
confidence: 72%
“…Interestingly, forest was the class optimized with the lowest resistance for both species. Although some studies have demonstrated that L. geoffroyi selects forested habitats in areas with human disturbance (Caruso et al, 2016; Manfredi et al, 2012; Tirelli et al, 2019), this result was still unexpected, since it is considered an open‐habitat species. In addition, forested areas are mainly found in the northern part of L. geoffroyi 's distribution, covering a small portion of the species' range.…”
Section: Discussionmentioning
confidence: 99%
“…It is traditionally considered an open-habitat species (Sunquist & Sunquist, 2002). However, some studies have demonstrated that in human-dominated landscapes, it selects closed vegetation within open habitats (Caruso et al, 2016;Manfredi et al, 2012;Tirelli et al, 2019). It also seems to be tolerant to some degree of habitat alteration (Pereira et al, 2011(Pereira et al, , 2012Sartor et al, 2021) and may sometimes benefit from it, expanding its occurrence and taking advantage of the higher prey density found in the border of agricultural areas (Caruso et al, 2016;Cuyckens et al, 2016).…”
Section: Study Species and Study Areamentioning
confidence: 99%
“…This may potentially be attributed to random effects; however, such an explanation seems unlikely. One of our designated study areas aligns with the location examined by one of the authors in a previous study (Tirelli et al 2019). Despite differences in sampling efforts, this raises concerns, particularly given that our study encompassed diverse locations.…”
Section: Predicting Occupancy In Unsurveyed Areasmentioning
confidence: 90%